Little Lift and Look Nosy Lion : with Big Flaps - Milbourne, Anna (London : Usborne, 2021)
This interactive board book follows a curious lion cub exploring the African grasslands. Along the way, he meets a giraffe, a baby elephant, and a warthog. With sturdy flaps to lift on every page, it encourages curiosity and helps little ones develop motor skills while enjoying a fun and engaging adventure.
Keywords: English